2011
DOI: 10.1051/0004-6361/201117239
|View full text |Cite
|
Sign up to set email alerts
|

GOODS–Herschel: an infrared main sequence for star-forming galaxies

Abstract: We present the deepest 100 to 500 μm far-infrared observations obtained with the Herschel Space Observatory as part of the GOODS-Herschel key program, and examine the infrared (IR) 3-500 μm spectral energy distributions (SEDs) of galaxies at 0 < z < 2.5, supplemented by a local reference sample from IRAS, ISO, Spitzer, and AKARI data. We determine the projected star formation densities of local galaxies from their radio and mid-IR continuum sizes. We find that the ratio of total IR luminosity to rest-frame 8 μ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

81
926
9
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 996 publications
(1,034 citation statements)
references
References 118 publications
81
926
9
1
Order By: Relevance
“…66 The Chandra imaging reaches Lx = 10 42 erg s −1 at z = 1.78, sufficient to detect weak AGNs. To see if an obscured AGN interpretation matches the available data, we examined the Spitzer/MIPS 24 µm, Herschel/PACS 100 and 160 µm, Herschel/SPIRE 250, 350 and 500 µm and the JVLA 1.4 GHz data [67][68][69] . We found no counterpart to z8 GND 5296 at any of these wavelengths.…”
Section: 22mentioning
confidence: 99%
“…66 The Chandra imaging reaches Lx = 10 42 erg s −1 at z = 1.78, sufficient to detect weak AGNs. To see if an obscured AGN interpretation matches the available data, we examined the Spitzer/MIPS 24 µm, Herschel/PACS 100 and 160 µm, Herschel/SPIRE 250, 350 and 500 µm and the JVLA 1.4 GHz data [67][68][69] . We found no counterpart to z8 GND 5296 at any of these wavelengths.…”
Section: 22mentioning
confidence: 99%
“…Our estimated errors are quite reasonable compared to the expected point source flux errors from HSPOT (also listed in Extended Table 3). Note that although in the SPIRE bands the confusion noise is 2-3 times higher than the photon noise, this can be mitigated by using a PACS 160-micron prior on the position 39 . We can further compare our noise estimates to those from other Herschel observations of similar depth.…”
Section: Infrared Flux Uncertainty Estimatesmentioning
confidence: 99%
“…In particular, many recent studies have been arguing the role played by AGN and BH accretion in galaxy formation and evo-lution and how these are connected with the star formation activity in galaxies (e.g. Delvecchio et al 2014;Elbaz et al 2011). Starburst sources characterised by a high SFR are likely to happen simultaneously or coexist with the presence of an AGN which has been demonstrated both theoretically and by the observations (e.g., Bower et al 2006;Farrah et al 2003;Brusa et al 2014) .…”
Section: Introductionmentioning
confidence: 96%
“…For this reason it has become more and more important to characterise the interplay between the star formation activity and the nuclear gravitational accretion activity. Moreover, many authors have shown that exists a correlation between M * and SFR that defines the so called Galaxy Main Sequence (Elbaz et al 2011) which appears to evolve with cosmic time. How galaxies are distributed in this parameter space is still debated and e.g., ?, have shown that many of the off-main sequence objects require the presence of an AGN to justify their properties.…”
Section: Introductionmentioning
confidence: 99%